(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Proper nutrition forms the basis of life activity in children and adults and is a crucial factor in ensuring resistance to physical and chemical factors of the external environment. Improper nutrition significantly reduces the effectiveness of treatment measures in cases of chronic diseases, injuries, major surgical interventions, and other conditions, and negatively impacts the duration of hospital stay. The accumulated experience indicates that, especially in surgical treatment strategies, correcting disturbances in the processes of nutrient exchange and adequately providing energy and plastic needs should hold a central place [1,2,3,4,5].